Body image perception among breast cancer patients after mastectomy: A phenomenology study - Wulandari, Shenda Maulina; Yunitasari, Esti; Kusumaningrum, Tiyas; Myint, Nyein Moh Moh; Subu, Muhammad Arsyad (Palembang MediRose Publisher, 2023)
Background: Breast cancer is the most common type of cancer among all cancers. Most breast cancer treatments involve surgery, which leads to changes in body shape. These changes can have an impact on body image after mastectomy, affecting the patients’ quality of life. Objective: This study aimed to explore the perception of body image of breast cancer patient after mastectomy. Methods: A qualitative phenomenological approach was employed in this study. A total of 15 post-mastectomy clients were recruited through purposive sampling technique. Data collection involved semi-structured interviews, which were recorded. The data were analyzed using the Van Mannen approach with the assistance of NVivo 12 Plus software. Results: The majority of the participants were in the elderly phase, with an average education level of junior high school. Most had a history of stage IIB breast cancer and, on average, had undergone mastectomy three years ago. This study identified the theme of body image, which consisted of four categories and eleven sub-categories. Conclusions: The description of body image in post-mastectomy clients includes beliefs, thoughts, feelings, and behaviors. This response is influenced by the belief in the importance of breasts, optimism regarding achieving one’s ideal self, thoughts about changes in the body, acceptance of oneself and those around us, enthusiasm for healing and comfort, and social roles.